1965
DOI: 10.1039/c19650000167
|View full text |Cite
|
Sign up to set email alerts
|

The biosynthesis of terrain

Abstract: INSPECTION of the formula (I) of terrein, fromAsfiergillus teweus Thom, suggests that it arises at least partly by the polyketide-fatty acid route.It is unusual in containing a five-membered ring since polyketides normally contain six-membered ones if any, because they are connected with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Traditional labeling experiments have provided evidence of these compounds’ unique biosynthesis. The incorporation of 14 C‐ and 13 C‐labeled acetate into 1 , 4 , and 5 showed that they are biosynthesized by way of a polyketide pathway (Scheme and Figure S1 in the Supporting Information) . The effective incorporation of 6‐hydroxymellein ( 6 ) into 1 and 5 showed that 6 is a very plausible biosynthetic intermediate .…”
Section: Introductionmentioning
confidence: 99%
“…Traditional labeling experiments have provided evidence of these compounds’ unique biosynthesis. The incorporation of 14 C‐ and 13 C‐labeled acetate into 1 , 4 , and 5 showed that they are biosynthesized by way of a polyketide pathway (Scheme and Figure S1 in the Supporting Information) . The effective incorporation of 6‐hydroxymellein ( 6 ) into 1 and 5 showed that 6 is a very plausible biosynthetic intermediate .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Until 2014, Hertweck and co-workers discovered the PKS biosynthetic pathway of terrein and revealed the gene terA as essential one be responsible for the biosynthesis of terrein. …”
Section: Resultsmentioning
confidence: 99%
“…8,9 Terrein represents another type of notable metabolites of A. terreus, which was firstly isolated in 1935 and structural determined in 1955. [10][11][12] Then, terrein and its analogues attracted considerable attention for their biosynthetic investigations, [13][14][15] and until 2014, Hertweck and co-workers illustrated the gene cluster responsible for the biosynthesis of terrein. 16 Besides, terrein and analogues also attracted much attention for their total syntheses [17][18][19][20] for their versatile bioactivities including inhibitor of plant growth, anti-microbial, anti-proliferative, and anti-oxidative activities.…”
Section: Introductionmentioning
confidence: 99%
“…These results strongly support that hydrogen exchange occurs in the 6'-methyl group, which has proven to be the chain-starter group for the heptaketide formation. Naturally, such hydrogen exchange with medium water might be promoted through either intermediate of polyketomethylene (2), benzophenones (3) or dienones (4) forms (scheme). Especially, deuterium at 3' and 5 position could be replaced by hydrogen in the medium water because of the presence of hydroxyl group(s) at the adjacent ortho position(s) in 3.…”
Section: Discussionmentioning
confidence: 99%